2017
DOI: 10.3803/enm.2017.32.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Dyslipidemia in Koreans

Abstract: The prevalence of hypercholesterolemia in Koreans 30 years old and over was 19.5% in 2015 according to the Korean Nutrition and Health Examination Survey, which means that one-fifth of adults had hypercholesterolemia. The prevalence of hypertriglyceridemia in adults 30 years of age and older was 16.8% in 2015, and men had a 2-fold higher prevalence of hypertriglyceridemia than women (23.9% vs. 10.4%). The awareness of hypercholesterolemia in Koreans was higher in women than among men (62.4% vs. 51.4%). It incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…Recent data from the Korean National Health and Nutrition Examination Survey (KNHANES) reported that, in 2016,19.9% of adults aged ≥30 years had hypercholesteremia and 40.5% had dyslipidemia [8]. The prevalence of dyslipidemia in Korea has increased in an age-dependent manner and is more evident in women aged ≥50 years [8][9][10][11]. The level of disease awareness was as low as 32.1% in men and 32.6% in women (aged 30-49 years) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the Korean National Health and Nutrition Examination Survey (KNHANES) reported that, in 2016,19.9% of adults aged ≥30 years had hypercholesteremia and 40.5% had dyslipidemia [8]. The prevalence of dyslipidemia in Korea has increased in an age-dependent manner and is more evident in women aged ≥50 years [8][9][10][11]. The level of disease awareness was as low as 32.1% in men and 32.6% in women (aged 30-49 years) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, it is estimated that more than 100 million adults have total cholesterol levels of 200 mg/dL or higher and 31 million adults with total cholesterol levels of 240 mg/dL or higher [1]. Similarly, a previous study estimated that 19.5% of adults in South Korea have dyslipidemia in 2015 [2]. Furthermore, dyslipidemia patients are at increased risk for cardiovascular disease (CVD), the leading cause of death globally.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dyslipidemia in young adults is relatively high, with estimations ranging from 12.0% to 13.0% 6, 7. Furthermore, several studies have reported that high serum cholesterol in young adults is associated with cardiovascular events in the future 8, 9, 10, 11.…”
mentioning
confidence: 99%